Essays in the metaphysics of mind - Kim, Jaegwon (Oxford : Oxford University Press, 2010)
Jaegwon Kim presents a selection of his essays from the last two decades, on a set of related topics for which he has played a leading role in shaping philosophical debate, such as emergence explanation, reduction, and mental causation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics; Philosophy of mind